Effect of longitudinal electrode arrangement on EHD-induced heat transfer enhancement in a rectangular channel. (February 2016) - Peng, Ming; Wang, Tian-Hu; Wang, Xiao-Dong
Highlights: EHD-induced heat transfer enhancement in a square channel is conducted. Design criteria for optimal longitudinal electrode arrangement are obtained. Heat transfer of the channel is enhanced by optimizing electrode arrangement. Abstract: In this study, heat transfer enhancement in a rectangular channel by electrohydrodynamics (EHD) is investigated. The numerical simulation deals with the effects of longitudinal position for single electrode, longitudinal arrangement for multiple electrodes, and electrode number with optimal longitudinal arrangement. A factor ξ defined as the ratio of average heat transfer coefficient with EHD to that without EHD is used to evaluate the level of EHD-induced heat transfer augmentation. The results show that the closer for the electrode to the inlet, the larger the ξ is. It is also found that there is a competition between the inlet-closed position requirement and large electrode gap requirement to determine the optimal longitudinal electrode arrangement. Based on this result, the design criterion for the optimal longitudinal electrode arrangement with given electrode number is proposed and justified. The results also show that as the electrode number exceeds a certain value (7 in the present paper), the ξ w ith the optimal electrode arrangement reaches a plateau; further increasing the electrode number only increases the power consumption but has no contribution to the heat transfer enhancement. The results indicated here are limited to the geometry and the parameter range used in the present study.